Influence of a non-rotating shoulder on heat generation, microstructure and mechanical properties of dissimilar AA2024/AA7050 FSW joints. Issue 1 (January 2018) - Barbini, Alessandro; Carstensen, Jan; dos Santos, Jorge F.
Abstract: Friction stir welding (FSW) and stationary shoulder friction stir welding (SSFSW) were carried out for the butt joining of dissimilar AA2024-T3 and AA7050-T7651 aluminium alloys with thicknesses of 2 mm. A comparison between the two processes was performed by varying the welding speed while keeping the rotational speed constant. Through the analysis of the force and torque produced during welding and a simple analytical model, it was possible to show that in SSFSW there is more effective coupling with the tool and the heat produced is more efficiently distributed. This process decreases both the welding area and the diffusion at the interface of the two alloys compared with FSW. The minimum microhardness occurred at the advancing side (AS) at the interface between the thermo-mechanically affected zone (TMAZ) and the stir zone (SZ) in both processes, although the decrease was more gradual in SSFSW. This interface is also where all specimens failed for both welding technologies. An increase in tensile strength was measured in SSFSW compared with standard FSW. Furthermore, it was possible to establish the mechanical performance of the material in the fracture zone using digital image correlation.